A scoping review of studies evaluating the education of health professional students about public health. (January 2020) - Evashwick, C.; Tao, D.; Perkiö, M.; Grivna, M.; Harrison, R.
Abstract: Background: The purpose of this article is to identify and describe key components of research into the teaching methods of public health to postgraduate students. Study design: This is a systematic review of the published literature. Methods: A detailed search of the literature based on keywords, Boolean operators, and free-text terms, identified from PubMed, Scopus and ERIC, published in the English language, between January 2000 and December 2017, was made. Teams of independent pairs agreed studies eligible for the review and performed data extraction. Results: Of the 2, 442 potential studies on education of public health professionals, 86 met all the inclusion criteria. Specific study designs, data collection, and techniques for data analysis varied widely across the individual studies, and there was a lack of consistency on the whole. The number of students in each study ranged from ten to 1, 300. Forty-seven studies used quantitative methods to assess the effectiveness of teaching. Curriculum evaluation was the most common focus (n = 33), followed by course evaluation (n = 22). Few studies considered inequalities in terms of the types of students registered on the different courses/programs, with just three evaluating strategies to increase students from minority ethnic groups. Most studies evaluated short-term or medium-term outcomes rather than long-term impacts of education on students' careers or the relationship of education in meeting future public health workforce demands. Conclusions: This comprehensive systematic review identified a dearth of the literature on evaluations of approaches for teaching public health to health professions students. Those studies that had been published varied to such an extent in terms of their aims, methods, analysis, and results such that it was impossible to make any consistent comparisons of the observations reported in the studies. We conclude that evidence-based approaches for teaching public health to health professions students are either not sought by faculty and programs or, if conducted, not shared. As such, there are likely to be missed opportunities for ensuring that future graduates of health professions programs are as well prepared as possible to contribute to the health of the public. Highlights: Higher education for public health graduates needs to be based on evidence of effectiveness. We did a systematic review of the literature to examine current approaches and outcomes with this aim in mind. The review found a distinct lack of research on this topic. Public health graduate education has limited research and dedicated journals, yet common for other.